Legal professions work, structure and organization - Van Hoy, Jerry (Sociology of crime, law, and deviance ;, 2001)
During recent decades legal professions have changed dramatically. Legal work has become more specialized, women have entered legal professions in large numbers, and the number of nonwhite legal practitioners has increased. Equally important as the demographic changes among legal professionals, have been movements in several countries to make legal practice more responsive to competitive markets for services - both nationally and globally. This volume introduces a collection of research articles that explore the important changes among legal practitioners in the US, England, Germany and Canada. The articles are organized around three general themes: changes in the structure and organization of legal professions and legal practices (in the US, England and Germany); legal culture, professional time and job satisfaction (in the US and England); and the changing nature of legal work practices in various fields of law. The volume addresses many of the newest and most exciting themes in the sociology of law, including the global law firm, the dilemma of part-time employment for legal professionals, the sociolegal construction of time, and the unique dynamics of legal practices in different fields of law.